Can anything beat white? : a Black family's letters - Petry, Elisabeth (Margaret Walker Alexander series in African American studies., 2005)
Ann Petry (1908-1997) achieved prominence during a period in which few black women were published with regularity in America. Her novels, along with various short stories and non-fiction, poignantly described the struggles and triumphs of middle-class blacks living in primarily white communities. Petry's ancestors, the James family, served as inspiration for much of her fiction. This collection of more than four hundred family letters, edited by Petry's daughter, is an engaging portrait of black family life from the 1890s to the early twentieth century.